2009
DOI: 10.1021/je900572c
|View full text |Cite
|
Sign up to set email alerts
|

Solid−Liquid Phase Equilibria of N-Methylephedrine Enantiomers in Two Chiral Solvents

Abstract: The ternary solubility phase diagrams of the N-methylephedrine species in two chiral solvents, (S)-ethyl lactate and (2R,3R)-diethyl tartrate, have been studied. Solubility measurements were performed for enantiomeric compositions and temperatures ranging from 1:1 mixtures to the pure enantiomer and from (273 to 313) K. Predicted ideal solubility curves of the N-methylephedrine species in both solvents revealed deviations from experimental data. The nonrandom two-liquid model was applied to quantify and parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Table 1 further contains thermodynamic information not acquired in our lab for Tröger's base discussed below as a model compound. [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169] The systems studied show a wide variety of characteristics, such as polymorphy of the (Tables 1 and 2), which are both racemic compoundforming systems. In case of 3-chloromandelic acid for both the enantiomers and the racemic compound monotropic modifications exist.…”
Section: Illustration Of Selected Melt and Solution Equilibriamentioning
confidence: 99%
“…Table 1 further contains thermodynamic information not acquired in our lab for Tröger's base discussed below as a model compound. [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169] The systems studied show a wide variety of characteristics, such as polymorphy of the (Tables 1 and 2), which are both racemic compoundforming systems. In case of 3-chloromandelic acid for both the enantiomers and the racemic compound monotropic modifications exist.…”
Section: Illustration Of Selected Melt and Solution Equilibriamentioning
confidence: 99%
“…The 70:30 ratio was ascertained by checking the optimum viscosity of the [( S )-2-Pro-Me]­[NTF 2 ] chiral ionic liquid. The method used to perform the solubility equilibria was published in our previous articles. , It signifies an isothermal method, where a mixture comprising a 5 mL solvent and a considerable excess of the solid phase (weighing of the solid phase with an analytical balance, resolution of balance: ±0.01 mg) was placed into a thermostated vial, which was agitated by a magnetic stirrer and maintained at isothermal conditions (with an uncertainty: ±0.1 K, thermostat, RC6 CP Lauda, Germany) until equilibrium was attained. Subsequently, the solid and liquid phases were separated with a glass filter (pore size, 10 μm) and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, enantioselective crystallization is seen as a suitable method for the separation of enantiomers. Unfortunately, all efforts channeled in our previous work into the application of chiral solvents in direct enantioselective crystallization from solution as a possible way for the separation of the N -methylephedrine enantiomers have been proven to be unsuccessful. Therefore, there is the need to apply a suitable solvent that would be able to promote chiral recognition (asymmetry in the ternary solubility phase diagram) in the N -methylephedrine system. Recently, Vasiloiu et al reported that chiral ionic liquids can demonstrate strong chiral interactions, and also Reichert et al examined the prospect of applying complex solvents such as ionic liquids for crystallization processes.…”
Section: Introductionmentioning
confidence: 99%
“…This composition change may influence the solubility of the enantiomers and thus the crystal product yield. Furthermore, design of the hybrid process must consider the shift of eutectic composition by the change of the solvent composition. , Finally, the solvent where the composition has changed cannot be recycled back to the SMB process without readjusting the composition. To avoid such complexity caused by evaporation, employing continuous nanofiltration units may partly resolve this problem if the molecular size difference between solvents is not significant.…”
Section: Introductionmentioning
confidence: 99%
“…eq, column (10) competitive Langmuir isotherm , m = feed, des, ext, raf is a binary variable which equals one only if the stream is supplied to or withdrawn from column k. product concentration (16) cyclic steady state for liquid phase cyclic steady state for adsorbent…”
Section: ■ Introductionmentioning
confidence: 99%